Gerenciamento de resíduos semi-sólidos oriundos de oficinas mecânica da cidade de Pau dos Ferros-RN - Cartaxo, Aparecida Evangelista (Universidade Federal Rural do Semi-Árido, 2017)
The usefulness of lubricating oil for maintenance of automotive vehicles is indispensable and its use has grown significantly in the last few decades, due to the increased number of vehicles travelling around these days. The used or contaminated lubricating oil, popularly known as "burned oil", is one of the environmental concerns of our society. This waste when discarded incorrectly brings serious impacts to the environment, as it can contaminate soil, rivers, water tables and also have a great impact on human health. Machine shops and other companies in this field have great responsibility in the final destination of contaminated oil, because they work directly with the waste and its consumers. The city of Pau dos Ferros/RN hosts 43 companies in the field of machine shops that are registered according to the Municipal Tax Office. Given the problematic of the subject, the management of the lubricating oil in 30 establishments of the city was analyzed. It was possible to observe the lack of information by owners and employees about legislation and tools that help in the proper final disposal of the waste, as well as the lack of inspection in the institutions that work with that oil, factors that could cause serious damage to the environment.
Keywords: Óleo lubrificante usado ou contaminado; Gerenciamento; Meio ambiente; Contaminated or used lubricating oil; Management; Environment; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA